1995
DOI: 10.1002/anie.199511711
|View full text |Cite
|
Sign up to set email alerts
|

Basic Principles of Thermoanalytical Techniques and Their Applications in Preparative Chemistry

Abstract: The investigation of thermodynamic properties and reactivity yields interesting insights into the chemistry of newly synthesized substances. With thermal analysis extensive information can be gained from small samples (often only a few milligrams). In addition, the data obtained by thermal analysis can be used to plan and optimize a synthesis. Among the most important applications are identification and purity analysis, and the determination of characteristic temperatures and enthalpies of phase transitions (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 114 publications
0
73
0
2
Order By: Relevance
“…DSC and TGA data were recorded with a MettlerToledo DSC821 instrument and treated by standard methods. [33] Elemental analyses were conducted with a Carlo Erba EA1110 instrument.…”
Section: Experimental Section General Remarksmentioning
confidence: 99%
“…DSC and TGA data were recorded with a MettlerToledo DSC821 instrument and treated by standard methods. [33] Elemental analyses were conducted with a Carlo Erba EA1110 instrument.…”
Section: Experimental Section General Remarksmentioning
confidence: 99%
“…The principal applications in this area have included determining the degree of purity of drugs (Windmann, Scherrer, 1991), the conducting of the analyses of thermal stability and the kinetics of decomposition, the study of possible drug-drug and/or drug-excipient interactions in the pre-formulation phase (Iglesias et al, 1998;Saesma et al, 1991;Araújo et al, 2003), and in the characterization of raw materials and finished products (Ford, Timmins, 1989;Canotilho et al, 1992;Cammenga, Epple, 1995;Giron, , 1999Brown, Glass, 1999;Thompson, 2000). Canotilho and collaborators (1992) reported that the resources and potential of thermal analysis in the pharmaceutical field are considerable not only for the study of polymorphism, but also for their versatility in other applications.…”
Section: Introductionmentioning
confidence: 99%
“…The relation of the absolute glass transition temperature to the melting temperature allows within limits for information on the structural properties of amorphous networks. For highly symmetric polymers, made up from small monomeric units, T g /T m is generally 0.5 or lower, for the broad majority of polymers, however, this relation amounts 2/3 [22]. For the amorphous TlBi 2 Cl 7…”
Section: Structural Investigations Of the Glassy Tlbi 2 CLmentioning
confidence: 99%